Effectiveness and safety of East Asian herbal medicine for menopausal insomnia: a systematic review and meta-analysis - Kwon, Chan-Young; Lee, Boram; Lee, Ji-Yeon (Frontiers in Pharmacology, 2024)
Background: Menopausal insomnia significantly impacts the quality of life in women. East Asian herbal medicines (EAHMs) have been traditionally used in Asian countries, but their efficacy and safety require systematic evaluation. This systematic review and meta-analysis aimed to evaluate the effectiveness and safety of EAHM for treating menopausal insomnia. Methods: A comprehensive literature search was conducted across 10 electronic databases from inception until 19 July 2023. Randomized controlled trials (RCTs) investigating EAHM for menopausal insomnia were included. Two reviewers independently screened studies, extracted data, and assessed the risk of bias using the Cochrane risk of bias tool. The primary outcome was sleep quality, insomnia severity, and sleep architecture. Secondary outcomes included total effective rate (TER), menopausal symptoms, and adverse effects. Meta-analysis was conducted using a random-effects model, and the results were calculated as mean differences (MDs) or risk ratios (RRs) and their 95% confidence intervals (CIs). Also, the certainty of evidence was assessed using the GRADE approach. Results: A total of 70 RCTs involving 6,035 participants met the inclusion criteria. The most frequently used EAHMs were modified Suan Zao Ren Tang, and the most frequently used herbal component was Zizyphus jujuba Miller var. spinosa Hu ex H. F. Chou [Rhamnaceae; Zizyphi Semen]. Compared with sedative-hypnotics, EAHM significantly improved sleep quality, as measured by the Pittsburgh Sleep Quality Index (PSQI) (MD –2.18, 95% CI –2.56 to −1.80), and reduced menopausal symptoms, as assessed by the Kupperman Index (MD –4.92, 95% CI –6.03 to −3.80). Similar results were seen when EAHM was added to sedative-hypnotics. When EAHM was additionally used in sedative-hypnotics, similar benefits were shown for PSQI (MD –2.46, 95% CI –3.09 to −1.82) and the Kupperman Index (MD –4.64, 95% CI –5.07 to −4.21). EAHM was generally safer than sedative-hypnotics, with significantly fewer adverse reactions (RR 0.15, 95% CI 0.07–0.34). However, the certainty of evidence was moderate to low. Conclusion: EAHMs, alone or with sedative-hypnotics, may be effective and safe for improving sleep quality and managing menopausal symptoms. Future studies should include diverse populations, rigorous methodologies, and explore mechanisms of action to confirm these findings. Systematic Review Registration: [https://www.crd.york.ac.uk/prospero/display_record.php?], identifier [CRD42023446708].